Consumers' Understanding of FDA Approval Requirements and Composite Scores in Direct-to-Consumer Prescription Drug Print Ads. Issue 8 (2nd August 2016) - O'Donoghue, Amie C.; Sullivan, Helen W.; Williams, Pamela A.; Squire, Claudia; Betts, Kevin R.; Fitts Willoughby, Jessica; Parvanta, Sarah
Abstract : In 2 studies, we investigated how laypersons perceive the Food and Drug Administration (FDA) approval process, FDA authority, and the presentation of composite scores in direct-to-consumer (DTC) prescription drug print ads. The 1st study consisted of 4 focus groups ( N = 38) in 2 cities. Using a semi-structured guide, a moderator led participants through the viewing of 3 existing DTC print ads that differed in the presence or absence of composite score information, and participants discussed their views of the ads and their understanding of composite scores. The 2nd study surveyed a nationally representative sample of 1, 629 individuals from the general population who saw a fictitious DTC print ad and answered closed-ended questions about the same topics. Results showed that knowledge of FDA approval and authority was mixed, with several misconceptions apparent. Many consumers were not familiar with the use of composite scores in a medical context or in advertising and, in the 1st study, expressed distrust of the product and the ad after learning about how composite scores are used. In the 2nd study, receiving composite score information changed the perceived clarity of the ad but not the perceived risk or benefits. Implications for the presentation of complex medical information are discussed.